أثر المنصب على عملية اتخاذ القرار لدى العاملين في المؤسسات الرياضية في الجمهورية العربية السورية - إبراهيم, قاسم; وطفي, ألفت; ماشي, عصام (Latakia University Journal -Medical Sciences Series, 2016)
القرار هو أحد الوظائف الإدارية التي يعتمد عليها العمل الإداري , إذ أن جميع الأعمال والوظائف والإجراءات الإدارية هي عبارة عن قرارات يتم اتخاذها في مختلف المستويات الوظيفية.إذ أنه لا يقتصر على فئة محددة من الإداريين أو مستوى معين في الهيكل التنظيمي , فهو عمل يقوم به الرئيس والمرؤوس في آنٍ واحد.لذا فإن هذه الدراسة تعنى بالتعرف على أثر المنصب على طريقة اتخاذ القرار لدى العاملين في المؤسسات الرياضية في الجمهورية العربية السورية , بالإضافة إلى أنه يعالج مشكلة عدم معرفة العلاقة بينهما.شملت عينة الدراسة 102 من العاملين في القيادات الرياضية في الاتحاد الرياضي العام 39 منهم بمنصب الرئيس , و63 منهم بموقع المرؤوس , حيث تم تصميم استبيان وتوزيعه على العاملين في المؤسسات الرياضية وتم جمع الاستبيان من قبل الباحث.وتوصلت الدراسة إلى وجود فروق بين من هم بمنصب الرئيس ومن هم بموقع المرؤوس ولصالح منصب الرئيس إذ تبين أن درجة متوسط القرار للرئيس أعلى من متوسط درجة القرار للمرؤوس.The decision is one of the administrative functions which the administrative work depends on, as all business, functions and administrative procedures is a decisions taken at various job levels.As it is not limited to a specific category of the administrator or a certain level in the organizational structure, it is a work done by superior and subordinate at once.Therefore, this study is concerned identify the impact of the position on the way decision-making among workers in the sports institutions in the Syrian Arab Republic, as well as it addresses the problem of lack of knowledge of the relationship between them.The study sample included 102 of the workers in the sports leaders in the General Sports Federation 39 of them in the position of president, and 63 of them in subordinate position, where the questionnaire was designed and distributed to workers in the sports institutions and the questionnaire were collected by the researcher.The study found the existence of differences between the position of the President are those of the rank subordinate and in favor of the position of President where it was found that the average degree of resolution to President higher than the average degree of resolution of a subordinate